Analysis of Stress Concentration of Laminated Composite Plate With Circular Hole - Rameshwari Vivek Lalge; Dr. D. N. Kamble (International Journal of Innovations in Engineering Research and Technology, 2021)
Composite materials are finding a wide range of applications in structural design, especially for lightweight structure that have stringent stiffness and strength requirements. They are attractive replacement for metallic materials for many structural applications. By finding efficient composite str ucture design that meets all requirements of specific application. This is achieved by tailoring of material properties through selective choice of orientation, no. of stacking sequence of layers that make up composite material. Composites are used more and more often for load carrying and safety structures in all kind of applications foe aviation and space technology, for vehicles etc. Composite materials have been introduced progressively in automobiles, followingpolymer materials, a few of which have be en used as matrices. It is interestingto examine the relative masses of different materials which are used in theconstruction of automobiles. Even thoughthe relative mass of polymer - based materials appears low, one needs to take intoaccount that the specif ic mass of steel is about 4 times greater than that of polymers.This explains the higher percentage in terms of volume for the polymers.